THE EFFECT OF INTERACTIVE LEARNING MEDIA ON STUDENT’S CONCEPTUAL UNDERSTANDING - Sriyani, Dewi; Koto, Irwan; Defianti, Aprina; Sakti, Indra; Uliyandari, Mellyta (Journal of Teaching and Learning Physics, 2023)
The objective of the study was to determine the effect of interactive learning media on the conceptual understanding of the pressure on substances for Grade VIII students. This type of research was a quasi-experimental design with a non-equivalent control group design involving the experimental and control groups. The experimental group was exposed to an interactive media storyline 3 integrated with PhET simulation, while the control group used the presentation graphic (PowerPoint). A total of 62 students from the state junior high school in Bengkulu Tengah district in Bengkulu province. The data collection instrument was a conceptual understanding test. The data analysis technique employed the independent t-test and Cohen’s effect size. The result of the effect size test indicates that the use of storyline 3 interactive media integrated with PhET simulation induced students' conceptual understanding of class VIII on the concepts of pressure indicated by the effect size with large criteria (d = 1.082).